Gamete-exporting organs of vertebrates: dazed and confused - Kanamori, Akira; Kobayashi, Yasuhisa (Frontiers in Cell and Developmental Biology, 2023)
Mature gametes are transported externally for fertilization. In vertebrates, the gonads are located within the coelom. Consequently, each species has specific organs for export, which often vary according to sex. In most vertebrates, sperm ducts and oviducts develop from the Wolffian and Müllerian ducts, respectively. However, exceptions exist. Both sexes of cyclostomes, as well as females of basal teleosts, lack genital ducts but possess genital pores. In teleosts of both sexes, genital ducts are formed through the posterior extensions of gonads. These structures appear to be independent of both Wolffian and Müllerian ducts. Furthermore, the development of Wolffian and Müllerian ducts differs significantly among various vertebrates. Are these gamete-exporting organs homologous or not? A question extensively debated around the turn of the 20th century but now largely overlooked. Recent research has revealed the indispensable role of Wnt4a in genital duct development in both sexes of teleosts: zebrafish and medaka. wnt4a is an ortholog of mammalian Wnt4, which has functions in Müllerian duct formation. These results suggest a potential homology between the mammalian Müllerian ducts and genital ducts in teleosts. To investigate the homology of gamete-exporting organs in vertebrates, more detailed descriptions of their development across vertebrates, using modern cellular and genetic tools, are needed. Therefore, this review summarizes existing knowledge and unresolved questions on the structure and development of gamete-exporting organs in diverse vertebrate groups. This also underscores the need for comprehensive studies, particularly on cyclostomes, cartilaginous fishes, basal ray-finned fishes, and teleosts. This is a provisional file, not the final typeset article have genital pores, which are very short passages from the coelom to the urogenital sinus. Most jawed vertebrates use the Wolffian ducts (WDs) and Müllerian ducts (MDs) for sperm and ova export, respectively. Finally, most teleosts of both sexes have genital ducts that develop as posterior extensions of the gonads. The anatomical differences among these three types of structures have historically led to their classification as non-homologous organs in textbooks on vertebrate comparative anatomy (e.g.